Effect of silicon doping on the reactivity and catalytic activity of gold clusters - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Journal of Physical Chemistry C, 2014)
Doping is known to be an excellent and simple way of catalyst design. Although notable progress has been made in understanding the reactivity and catalytic activity of gas-phase and supported gold clusters, very few studies have been carried out on the doped gold clusters. In the present work, we have carried out density functional theory calculations to investigate the effect of silicon doping on the reactivity and catalytic activity of gold nanoclusters. The present work particularly focuses on the adsorption and activation of molecular oxygen on the pristine and silicon-doped gold clusters. The results confirm that the silicon-doped Au7Si cluster shows considerable binding and activation of the O-2 molecule in comparison to the pristine Au-8 cluster as reflected in the relevant geometrical parameters (O-O and Au-O bond lengths) and O-O stretching frequency. However, silicon doping has no contrasting effect on the reactivity and catalytic activity of the Au-7 cluster. In addition to the stronger binding and activation of the O-2 molecule, the doped Au7Si cluster leads to a significant reduction in the activation barrier (0.57 eV) for the environmentally important CO oxidation reaction in contrast to the catalytically inactive pristine Au-8 cluster (1.22 eV). Thus, our results highlight the critical role of doping foreign impurities for future endeavors in the field of gold nanocatalysis.

Enhanced interaction of molecular oxygen with amino acid complexes of silver and gold clusters - Manzoor, Dar; Pal, Sourav (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
Density functional theory calculations have been carried out to study the effect of amino acid adsorption on the reactivity of silver and gold clusters with molecular oxygen. It is found that the amino acids glycine and alanine form stable complexes with both Ag-4 and Au-4 clusters. However, the extent of interaction is more in the case of the Au-4 cluster, as reflected from the increase in binding energy in the amino acid Au-4 complexes. Our results confirm that the adsorption of amino acids glycine and alanine enhances the reactivity of Ag-4 and Au-4 clusters towards O-2 molecule. The enhanced reactivity of O-2 molecule towards the amino acid metal cluster complexes is manifested by an increase in the O-2 binding energy and a decrease in the M-O (M = Ag, Au) bond length. Moreover, it is found that the co-adsorption of amino acids and O-2 molecule on the Ag-4 and Au-4 clusters is cooperative.
Keywords: Amino acid complexes; Density functional calculations; Gold clusters; Metal clusters; Silver clusters; Theoretical chemistry

Endohedrally doped gold nanocages: efficient catalysts for O-2 activation and CO oxidation - Manzoor, Dar; Krishnamurty, Sailaja; Pal, Sourav (Physical Chemistry Chemical Physics, 2016)
Gold nanocages are the most attractive catalytic materials as all the atoms in the cage type clusters reside on the surface, making them available for chemisorption by reacting molecules. Due to a hollow space at the center, their chemical and catalytic properties can be tuned effectively and easily by endohedral doping. While a significant experimental and theoretical understanding is currently available on the structural and electronic properties of doped gold cages, very little information is available on their reactivity and catalytic behavior. In the present work, with the help of density functional theory calculations we demonstrate that endohedral doping leads to a notable increase in the binding energy of molecular oxygen on the gold nanocages. The enhancement in the O-2 binding energy on the doped gold cages is also confirmed by a significant decrease in the Au-O and an increase in the O-O bond lengths, corroborated by a red shift (similar to 250 cm(-1)) in the O-O stretching frequency as compared to the pristine cage. Furthermore, interestingly, the doped gold cages show very low activation barriers for the environmentally important CO oxidation reaction as compared to the pristine gold cage. Importantly, the decrease in the barrier height is comparatively greater for the rate limiting step of O-O-C-O intermediate formation and as a result the CO oxidation is expected to be more facile on the doped gold cages. Thus, the current study highlights the role of heteroatom doping in imparting new chemical and catalytic properties to gold cages and is expected to spur further research in the design of efficient gold nanocatalysts.